MYCOREMEDIATION OF DIESEL CONTAMINATED SOIL WITH OYSTER MUSHROOM (PLEUROTUS OSTREATUS) USING MAIZE (ZEA MAYS) AS THE TEST CROP - Seidu, A.; Quainoo, A. K.; Addae, G.; Stenchly, K. (UDS International Journal of Development, 2016)
The remediation of soil contaminated with petroleum based compounds by oyster mushroom (Pleurotus ostreatus) has been well documented. In this study the ability of diesel contaminated media treated with mushroom to support plant growth was investigated using maize as test crop. The mushroom was grown on different levels of dieselÂ (14ml, 29ml, 58ml, 106ml and control), each to 500g of soil ( contaminated media). Each of the five samples (RS 14, RS 29, RS58, RS 106 and RS Control) was replicated five times. Another set of media with various diesel levels (14ml, 29ml, 58ml and 106ml) were formulated as above but they were not remediated by the mushroom spawn (NRS 14, NRS 29, NRS 58, NRS 106 and NRS Control).Â Data was subjected to analysis of variance (ANOVA) using Genstat statistical package and treatments were compared at 5% probability level. The highest removal of petroleum hydrocarbons by oyster mushroom was most pronounced in the 29ml level of diesel contamination which recorded the highest germination percentage (100%) of the maize seeds. The least reduction in hydrocarbons was in the 58ml and 106ml media, which did not record any germination of maize seeds. There was a reduction in the toxicity of the soils treated with Pleurotus ostreatus, since the mycelium was able to run through all the treatments, even though the maize seeds did not grow on remediated soil of 58ml diesel (RS58) and remediated soil of 106ml diesel (RS106). Germination of the seeds of the test plant in 29ml and 14ml diesel fuel contaminated substrates was higher than in the control. Growth of the maize plant was inhibited on the contaminated soils which however differed significantly (p < 0.05) from those of the control.Â Â Keywords: Remediated media, Non remediated media, Mushroom, Maize, Mycoremediation